Epigenetic roles in clonal hematopoiesis and aging kidney-related chronic kidney disease - Ogura, Yoshiyasu; Mimura, Imari (Frontiers in Cell and Developmental Biology, 2023)
Accumulation of somatic hematopoietic stem cell mutations with aging has been revealed by the recent genome-wide analysis. Clonal expansion, known as clonal hematopoiesis of indeterminate potential (CHIP), is a premalignant condition of hematological cancers. It is defined as the absence of definitive morphological evidence of a hematological neoplasm and occurrence of ≥2% of mutant allele fraction in the peripheral blood. In CHIP, the most frequently mutated genes are epigenetic regulators such as DNMT3A, TET2, and ASXL1. CHIP induces inflammation. CHIP is shown to be associated with not only hematological malignancy but also non-malignant disorders such as atherosclerosis, cardiovascular diseases and chronic liver disease. In addition, recent several large clinical trials have shown that CHIP is also the risk factor for developing chronic kidney disease (CKD). In this review article, we proposed novel findings about CHIP and CHIP related kidney disease based on the recent basic and clinical research. The possible mechanism of the kidney injury in CHIP is supposed to be due to the clonal expansion in both myeloid and lymphoid cell lines. In myeloid cell lines, the mutated macrophages increase the inflammatory cytokine level and induce chronic inflammation. It leads to epigenetic downregulation of kidney and macrophage klotho level. In lymphoid cell lines, CHIP might be related to monoclonal gammopathy of renal significance (MGRS). It describes any B cell or plasma cell clonal disorder that does not fulfill the criteria for cancer yet produces a nephrotoxic monoclonal immunoglobulin that leads to kidney injury or disease. MGRS causes M-protein related nephropathy frequently observed among aged CKD patients. It is important to consider the CHIP-related complications such as hematological malignancy, cardiovascular diseases and metabolic disorders in managing the elderly CKD patients. There are no established therapies for CHIP and CHIP-related CKD yet. However, recent studies have supported the development of effective CHIP therapies, such as blocking the expansion of aberrant HSCs and inhibiting chronic inflammation. In addition, drugs targeting the epigenetic regulation of Klotho in the kidney and macrophages might be therapeutic targets of CHIP in the kidney.